Monetary Transaction Costs and the Term Premium - Espinoza, Raphael (IMF Working Papers; Working Paper ;, 2013)
We show that, in a monetary equilibrium, trade and asset prices depend on both the supply of the liquidity by the Central Bank and the liquidity of assets and commodities. As a result, monetary aggregates are informative for the conduct of monetary policy. We also show asset prices are higher in liquidity-constrained states of nature. This generates a term premium even in absence of aggregate uncertainty. These results hold in any monetary economy with heterogeneous agents and short-term liquidity effects, where monetary costs act as transaction costs and the quantity theory of money is verified.